1991
DOI: 10.1007/bf01986346
|View full text |Cite
|
Sign up to set email alerts
|

Behavior and growth ofMercenaria mercenaria during simulated storm events

Abstract: Abstract. Experiments were conducted in April August 1989 on juvenile Mercenaria mercenaria (L.) in an oscillatory water tunnel to simulate resuspension of bottom sediments by waves and to determine the effects of shortterm storm events on particle ingestion, pseudofeces production, and shell growth. Juveniles (mean length= 19.2 mm) were subjected to identical concentrations of algae in both low-flow, gentle waves (maximum velocity = 7 cm s -1) and high-velocity storm waves (maximum velocity = 22 cm s -1). Sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…Field measurements have demonstrated that regular resuspension of the fine sediment at the Frisian Front dilutes food concentrations and lowers food quality for suspension feeders (Duineveld & Boon 2002). This may explain the depressed growth rates in fine-grained sediments, as is the case in other areas with frequent resuspension (Emerson 1990, Turner & Miller 1991, Bock & Miller 1994, Urrutia et al 1996, Grant et al 1997, Cranford et al 1998, Gremare et al 1998.…”
Section: Discussionmentioning
confidence: 99%
“…Field measurements have demonstrated that regular resuspension of the fine sediment at the Frisian Front dilutes food concentrations and lowers food quality for suspension feeders (Duineveld & Boon 2002). This may explain the depressed growth rates in fine-grained sediments, as is the case in other areas with frequent resuspension (Emerson 1990, Turner & Miller 1991, Bock & Miller 1994, Urrutia et al 1996, Grant et al 1997, Cranford et al 1998, Gremare et al 1998.…”
Section: Discussionmentioning
confidence: 99%
“…This resuspended particulate matter can cause heavy mortality by blocking the gills of bivalves (Tang & Fang 2002). Turner and Miller (1991) reported that hard clam Mercenaria mercenaria under simulated storm showed up to a 38% reduction in shell growth compared with clams under gentle wave conditions. They pointed out that the decrease was probably caused by a reduction in filtration rate coupled with a decrease in net energy gained from filtration because of costs of pseudofeces production.…”
Section: Factors Affecting Growthmentioning
confidence: 97%
“…Suspended-sediment concentrations required to elicit these responses and mortality, however, are extremely high, i.e., beyond the upper limits of concentrations reported for most estuarine systems under natural conditions and typical concentrations associated with dredging operations. Sublethal effects, such as reduced pumping rates and growth, were evident for adult bivalves at concentrations that occur under natural conditions, but may be of short-term (hours to days) duration, for example, during a storm (Schubel 1971;Turner and Miller 1991). As with estuarine fish, the egg and larval stages of shellfish are more sensitive to suspended-sediment impacts than the adults.…”
Section: Integrating Biological and Dredging Project Datamentioning
confidence: 99%
“…Primary mechanisms used by bivalves to deal with high suspended-sediment concentrations include the reduction of net pumping rates (Foster-Smith 1976) and rejection of excess filtered material as pseudofeces (Robinson, Wehling, and Morse 1984;Turner and Miller 1991;Hawkins et al 1996). When suspended-sediment concentrations rise above a threshold at which bivalves can effectively filter material, a dilution of the available food occurs (Widdows, Fieth, and Worrall 1979).…”
Section: Juvenile and Adult Stagesmentioning
confidence: 99%